Optimum sintering temperature of high quality silicon nitride ceramics under oscillatory pressure. Issue 6 (15th April 2018) - Han, Yao; Xie, Zhipeng; Li, Shuang; Zhu, Tianbin; Wu, Weiwei; An, Di; Hu, Feng; Zhai, Fengrui
Abstract: High quality silicon nitride ceramics were fabricated by an oscillatory pressure sintering (OPS) process and the effect of sintering temperature on the microstructure and mechanical properties of Si3 N4 ceramics was investigated. Different from the specimen fabricated by the conventional hot pressing (HP) method, only β-Si3 N4 grains were detected in all the OPS-fabricated specimens. Driving forces of densification and grain growth were accelerated aided by oscillatory pressure. The optimum sintering temperature for silicon nitride ceramics under oscillatory pressure is considered to be 1770 °C; the highest average aspect ratio of β-Si3 N4 grains (4.74) was achieved from the highly densified compact (99.86% of theoretical density). The specimen prepared at this temperature accompanied with the highest flexural strength, hardness and fracture toughness of 1348 MPa, 16.04 GPa and 12.8 MPa m 1/2, respectively. The presence of oscillatory pressure is detected to promote the elimination of defects and accelerate the densification and grain growth kinetics of grains, thus contributing to the improvement of mechanical properties.